Implementasi Adab Berdialog Menurut Muhammad Sayyid Thanthawi Melalui Pembelajaran Siswa Aktif - Moh. Erfan Maulana; Abuddin Nata; Adian Husaini; E.Bahruddin (Rayah Al-Islam, 2020)
Dialogue is a method of learning that involves students to be active, both cognitive, affective, and psychomotoric. But in practice dialogue sometimes leads to conflicting attitudes and provoking emotions. This study is aimed to explore dialogue concept of Muhammad Sayyid Tantawi in his book Adab Hiwar fi al-Islam and the implementation of the dialogue concept into active learning at school. The finding showed that there are eleven rules of dialogue concept which according to Muhammad Sayyid Tantawi, namely: (1) Honesty, (2) Focus on the themes discussed, (3) Presenting an accurate proposition and sound logic (4) Clarify the location of differences in a concrete and correct manner according to the discussion (5) Ethics of politeness, avoiding actions that are not appropriate to do, (6) Lead to the public interest, (7) Prioritize the opinions of expert experts, (8) Do not generalize the law, (9) Reviewing the principles of benefits and their disadvantages, (10) Upgrading the understanding and accuracy of the law agreed upon by the experts (11) Being open and candid, by promoting the truth.